A retrospective review of the most common safety concerns encountered at a range of international recompression facilities when applying the Risk Assessment Guide for Recompression Chambers over a period of 13 years - Burman, Francois (Stellenbosch : Stellenbosch University, 2014)
Thesis (MScMedSc)-- Stellenbosch University, 2014.